Cultural Peace in the Cap Go Meh Celebration Among the Multiethnic Community on Kemaro Island, Palembang - Abrar, M. Faqih (Arbain Publishing, 2025)
The Cap Go Meh celebration on Kemaro Island attracts attention because it is attended by people from various cultural backgrounds, creating a unique multiethnic phenomenon. This diversity raises questions about the reasons behind the participation of multiethnic communities in the celebration. This research uses the Cultural Peace theory developed by Johan Galtung as the main analytical framework. This theory emphasizes the importance of cultural peace created through harmonious social interactions and mutual respect for differences. The results show that multiethnic communities visit Kemaro Island during Cap Go Meh with various purposes, namely visiting the graves of Siti Fatimah and Tan Bunn Ann, learning history, and also enjoying the atmosphere of the Cap Go Meh celebration which has many events such as lion dance. Cultural Peace works through the interactions of multiethnic communities who visit Kemaro Island during the Cap Go Meh event.